PENGENDALIAN PERSEDIAAN BAHAN BAKUDENGAN MENGGUNAKAN ACTIVITY BASED COSTING (ABC) ANALISIS PADA PT BESMINDO ANDALAS SEMESTA - syafri roni; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Inventory is one of the most expensive and important asset to a company both service companies and trading companies. Companies must focus on controlling inventory because the inventory is one part that absorbs the greatest investment. The purpose of this study is to determine control of raw materials by using ABC analysis on PT Besmindo Andalas Semesta. Using the Pareto principle, “the critical few and the trivial many”. The idea is to focus on inventory control to inventory items high value to low-value inventory.This study indicates that inventories are classified in category A have a percentage amount of inventory by 8.3% with the percentage value of 42.42%, category B have a total percentage of inventories amounted to 32.94% with the percentage value of 31.88%, category C has a number inventory percentage of 59.83% with a percentage value of 24.64%. So it can be concluded that the raw of materials in category A has a small amount with the absorption of large capital therefore the raw of materials in the development of category A should get more attention and kept well in comparison to the raw of material categories B and C.Keyword: Inventory Control, ABC Analisys